Perceived leadership characteristics of students majoring in Education at Universiti Putra Malaysia - Bakar, Ab. Rahim; Mohamed, Shamsiah (Universiti Putra Malaysia Press, 2004)
A study was conducted to assess the leadership characteristics of Universiti Putra students majoring in Education. The study showed that in general, UPM trainee teachers possess the leadership characteristics needed to function effectively as a leader. The study also showed that the trainee teachers' involvement in organizational activities was about average. It was also found that the leadership characteristics differed significantly among students with different level of participation in organizational activities, the perceived ability to manage the students' organizations, the perceived amount of knowledge the students have about the management of the organizations, the perceived importance of a student's organization, and the type of teacher education programs.